2009
DOI: 10.1111/j.1748-1716.2009.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Scn3b knockout mice exhibit abnormal sino‐atrial and cardiac conduction properties

Abstract: AimIn contrast to extensive reports on the roles of Nav1.5 α-subunits, there have been few studies associating the β-subunits with cardiac arrhythmogenesis. We investigated the sino-atrial and conduction properties in the hearts of Scn3b−/− mice.MethodsThe following properties were compared in the hearts of wild-type (WT) and Scn3b−/− mice: (1) mRNA expression levels of Scn3b, Scn1b and Scn5a in atrial tissue. (2) Expression of the β3 protein in isolated cardiac myocytes. (3) Electrocardiographic recordings in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 37 publications
4
50
0
Order By: Relevance
“…In addition, they found increased SA node recovery times and inducibility of atrial tachycardia and AF by burst pacing, extending the potential use of these animals as models for sick sinus syndrome (SSS) or AF. 79 In contrast to Scn1b null mice, no neurologic phenotypes were reported, suggesting that the most important functional roles of Scn3b may be in the heart. A recent study resolved the crystal structure of the b3 immunoglobulin domain, revealing that it assembles as a trimer in the crystal asymmetric unit.…”
Section: Animal Models Of Scn3bmentioning
confidence: 98%
“…In addition, they found increased SA node recovery times and inducibility of atrial tachycardia and AF by burst pacing, extending the potential use of these animals as models for sick sinus syndrome (SSS) or AF. 79 In contrast to Scn1b null mice, no neurologic phenotypes were reported, suggesting that the most important functional roles of Scn3b may be in the heart. A recent study resolved the crystal structure of the b3 immunoglobulin domain, revealing that it assembles as a trimer in the crystal asymmetric unit.…”
Section: Animal Models Of Scn3bmentioning
confidence: 98%
“…Mutations in SCN2B have been linked to atrial fibrillation (AF) and Brugada syndrome, suggesting a role for β2 in cardiac excitability (Watanabe et al 2009;Riuro et al 2013). Cardiac excitability is also abnormal in Scn3b null mice, suggesting a role for β3 in the heart (Hakim et al 2008(Hakim et al , 2010. Upon programmed electrical stimulation, ventricular tachycardia occurs in Scn3b null, but not wild-type, Langendorff-perfused hearts (Hakim et al 2008).…”
Section: Modulation Of Sodium Current and Excitability In Vivomentioning
confidence: 99%
“…Upon programmed electrical stimulation, ventricular tachycardia occurs in Scn3b null, but not wild-type, Langendorff-perfused hearts (Hakim et al 2008). Scn3b null hearts display atrial tachycardia during atrial burst pacing (Hakim et al 2010). Scn4b has been identified as a modifier gene for Long QT Syndrome (LQTS) resulting from a mutant Scn5a gene (Remme et al 2009).…”
Section: Modulation Of Sodium Current and Excitability In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…21 No other primary mutations in Na V -interacting subunits have been reported in humans with cardiac conduction disorders, despite the fact that several studies in mice found a crucial role of these proteins in the cardiac conduction system. SCN3B-knockout mice exhibit important intracardiac conduction abnormalities, 30 and, interestingly, in the SCN5A-1798insD mutant mice, differential expression of b4 was found to contribute to strain-dependent conduction defect. 31…”
Section: Cardiac Conduction Disordersmentioning
confidence: 96%